(untitled) (The Strategic Review for Southern Africa, 2023)
The AU Kampala Convention aims to ensure that the states that have signed the treaty protect and assist internally displaced persons (IDPs) in their regions to establish geopolitical security, which is threatened by the inevitability, volume and heterogeneity of forced displacement. This article interrogates the link between the Kampala Convention and the minimisation of interstate conflict through a political will to tackle the challenge of forced displacement amongst member states the cooperation and integration of which would contribute to geopolitical security. Thus, using secondary data, the author determines how addressing large-scale forced displacement in the region can improve geopolitical security. Thus, based on an extensive review of relevant IDP issues in Africa, attention is paid to displacement trends on the continent, factors precipitating displacement and the flow of IDPs across the region, a current analysis of the AU Kampala Convention framework, the challenges to African geopolitical security and responsibility-sharing amongst African states. The author concludes that there should be synergy between host and displaced communities for integration and the provision of opportunities for IDPs to regain their livelihoods. Therefore, African states need to adapt and implement, as a matter of urgency, national, regional and international policies to solve the challenges of internal displacement in Africa and ensure geopolitical security.